Calculation of Silo Wall Pressure considering the Intermediate Stress Effect - Shanshan Sun; Junhai Zhao; Changguang Zhang (Advances in Civil Engineering)
The reasonable determination of wall pressure is critical for the design of silo structures. In this study, the primary objective is to present four novel wall pressure coefficients based on four true triaxial strength criteria in the quasiplane strain state. These four strength criteria are the Drucker-Prager (D-P) criterion, the Matsuoka-Nakai (M-N) criterion, the Lade-Duncan (L-D) criterion, and the unified strength theory (UST), and they all consider the effect of the intermediate stress yet to different extent. These coefficients have a wide application range and are readily used to predict the distribution of wall pressure for deep and squat silos. Comprehensive comparisons are made between the predictions from the wall pressure coefficients described herein and experimental data reported in the literature as well as the results from the European, American, and Chinese silo standards or the Rankine and the modified Coulomb theories. It is found that the effect of the intermediate stress on the wall pressure is very significant for both deep and squat silos; the wall pressure of the D-P criterion is underestimated, whereas that of the Mohr-Coulomb (M-C) criterion is overestimated; the L-D criterion is recommended to be adopted to calculate the soil wall pressure.